Optimized Design of SoC-based Control System for Multi-axis Drive - Gu, Qiang; Li, Yesong; Niu, Panqing; Sun, Jiajiang (Elektronika ir Elektrotechnika, 2014)
This study presents an optimized system-on-chip (SoC) based multi-axis control system for permanent magnet synchronous motor (PMSM). The multi-axis control system becomes considerably complex with increasing controlled axes and complicated control algorithms. This paper aims to provide a balanced design considering control performance, hardware constrains and feasibility. To cope with this problem, the system design is optimized by using pipeline and time division multiplexing technology. Due to the optimized architecture and the computation capability of SoC, the performance of the whole system can be preserved. To demonstrate this, a SoC implementation of the control system is presented and comprehensively analyzed. Herein, the vector control in the current loop is explained and an anti-windup proportional-integral (PI) controller is adopted in the speed loop. The sampling frequencies of the current loop and the speed loop are 16 KHz and 4 KHz respectively. Consequently, the execution time is several microseconds with reasonable consumed resources. Experimental results are shown to prove the efficiency of the proposed SoC-based solution. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.4848